2008
DOI: 10.1038/oby.2008.355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Cellulose‐containing Weight‐loss Supplement on Gastric Emptying and Sensory Functions

Abstract: 2CM3, a highly cross-linked cellulose in capsule form, expands in the stomach to a size several fold of its original volume. It is purported to induce a prolonged feeling of satiation and a delay in gastric emptying, thus promoting weight loss. We examined whether CM3 delays gastric emptying (using the stable isotope 13 C-octanoic breath test) and whether it influences subjective feelings of appetite sensations (using visual analog scales, VASs). We performed a double-blind randomized placebo-controlled crosso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Variations in effects between fibres with the same chemical structure can likely be explained by differences in composition of the fibres, which also affects their physicochemical properties. For example, cellulose (a glucan) is usually insoluble and non‐viscous (31), whereas ethylhydroxyethyl cellulose and microcrystalline cellulose (32,33) are both soluble and viscous. Similarly, guar gum (a mannan) can be chemically modified to reduce its viscous properties and improve its practical applications without alteration of the polymer structure (34).…”
Section: Discussionmentioning
confidence: 99%
“…Variations in effects between fibres with the same chemical structure can likely be explained by differences in composition of the fibres, which also affects their physicochemical properties. For example, cellulose (a glucan) is usually insoluble and non‐viscous (31), whereas ethylhydroxyethyl cellulose and microcrystalline cellulose (32,33) are both soluble and viscous. Similarly, guar gum (a mannan) can be chemically modified to reduce its viscous properties and improve its practical applications without alteration of the polymer structure (34).…”
Section: Discussionmentioning
confidence: 99%
“…Functional fiber characteristics, such as water solubility, viscosity, gelling, water binding capacity, and fermentability, are expected to be pivotal in the regulation of satiety (e.g., Papathanasopoulos and Camilleri, 2010). Moreover, there are good reasons to assume that short-term satiety depends on other key characteristics (e.g., bulking due to high water binding capacity or gelling) (Berthold et al, 2008; Hoad et al, 2004) than longer-term satiety (e.g., fermentability)(Cani et al, 2006; 2009). Hence, the effect of fiber differs according to the type of fiber used, but it should be realized that added fibers to food products do not always behave in a manner similar to naturally occurring fibers (Slavin and Green, 2007).…”
Section: Developing Satiety Enhancing Food Productsmentioning
confidence: 99%
“…One previously published randomized trial of CM3 alginate showed weight loss of 3–4 kg more than placebo (18). In a recent crossover trial, Berthold et al showed no effect of acute administration of CM3 alginate on appetite sensations, or on GE (19). Given this contradictory information, and the fact that the effect of CM3 alginate on stomach volume and accommodation are unknown, the aim of this study was to evaluate the effects of CM3 alginate on gastric motor functions, appetite, satiation, and satiety gut hormones in overweight and obese adults.…”
Section: Introductionmentioning
confidence: 99%